Fluctuation of Green Algae and Effects on the Growth of Pacific White Shrimp (Litopenaeus vannamei) - Mia Pinandita; Dewi Nugrayani; Agung Cahyo Setyawan; Imam Marzuki (Journal Of Artha Biological Engineering, 2025)
Algae are eukaryotic organisms with chlorophyll. Green algae contain chlorophyll, allowing them to photosynthesize directly and provide shrimp ponds with food. This study is entitled Fluctuations of Green Algae and Effects on the Growth of Pacific White Shrimp (Litopenaeus vannamei) in CV. Cemarasewu Sumber Rejeki, Cilacap. This observational study Oct–Dec 2022 monitored a pond in Cilacap. Water green algae and Pacific White Shrimp samples were taken every seven days age 64–120 days. Algae density was calculated hemocytometer, while shrimp growth parameters MBW, ADG, FCR, SR and water quality temperature, pH, DO, salinity, nutrients were measured. Data were analyzed descriptively to observe the relationship between algae fluctuations and shrimp growth. The results of the study showed that green algae experienced fluctuations during the Pacific White Shrimp cultivation period. The presence of green algae can have a good effect on the growth rate of Pacific White Shrimp. The growth rate of Pacific White Shrimp in the research pond was classified as good. The results obtained by ADG in plot B13 0.39%, B14 0.45% and B15 0.38%. MBW in plot B13 30.75 g, B14 31.68 and B15 32.05 g. FCR in plot B13 1.42, B14 1.45 and B15 1.39 and SR in plot B13 66.7%, B14 71.5% and B15 70.7%.